An experimental demonstration of AAB renewal in children with autism spectrum disorder. Issue 1 (17th June 2018) - Cohenour, Jessica M.; Volkert, Valerie M.; Allen, Keith D.
Abstract : Operant renewal is a return of extinguished behavior due to changes in contextual stimuli that control the occurrence or nonoccurrence of a response. Well‐established in classical conditioning and operant research, renewal presents itself in three forms—ABA, ABC, and AAB—and poses threats to treatment maintenance where extinction procedures are utilized. As AAB renewal may be less likely to occur than ABA or ABC renewal, the current study sought to determine if AAB renewal would occur with three participants with Autism Spectrum Disorder who were taught a simple lever pull response. Results showed that lever pulls increased for two of three participants when we introduced novel stimuli (i.e., a light and a buzzer) to alter the contextual environment after extinction. These findings suggest that AAB renewal may account for some instances of response recovery after extinction and that the procedure of this study may be beneficial to the further study of renewal and the variables that affect its occurrence within a translational model.